Inovação, aprendizagem organizacional e capacidade de absorção: evidências em escolas públicas integrais de Pernambuco - Carvalho, Elisângela da Silva Araujo (2016)
In Brazil, the search for good quality education is an ongoing challenge, given the social, rich cultural diversity and educational gap still present today, especially in high school. In this context, the main objective of this research was to analyze how the whole public schools, subsidized by organizational learning and absorption capacity, are innovating in high school education in Pernambuco. Specifically, it seeks to: Understand the characteristics of the main innovations developed in the integrated public schools; Diagnosing the role of organizational learning in favor of innovations in integrated public schools; Analyze how the absorption capacity contributes to innovations in integrated public schools. To achieve these goals, the strategy study of multiple cases was adopted, addressing three high school public schools in the full program of Pernambuco, with high educational performance forward the educational reality. The main data collection techniques consisted of interviews, direct observation and document analysis. Data analysis occurred through individual and cross-analysis. The results showed that the surveyed schools are innovating with the development of various educational innovations, most of which is classified as incremental and improvements in services. These innovations are subsidized by organizational learning and absorption capacity. They were found several factors that act to the innovative processes such as the use of internal and external knowledge, teamwork, a sense of belonging and connectivity between different school segments, which fostered innovations in pedagogical dimensions and school management. In all three cases, there was the sharing of practices carried out by integral education program, coming from the field of study, in order to contribute to the qualification of high school, which makes the research relevant for academic and professional circles of stakeholders. We conclude that the study supports that contribute to the search for new innovative experiences for school organizations in order to offer tools that can assist in the search of absorption capacity and learning that generate satisfactory results for the realization of a high school full quality.